Mapping white matter damage distribution in neuromyelitis optica spectrum disorders with a multimodal MRI approach. (May 2021) - Cacciaguerra, Laura; Rocca, Maria A; Storelli, Loredana; Radaelli, Marta; Filippi, Massimo
Background: The pathogenetic mechanisms sustaining neuroinflammatory disorders may originate from the cerebrospinal fluid. Objective: To evaluate white matter damage with diffusion tensor imaging and T1/T2-weighted ratio at progressive distances from the ventricular system in neuromyelitis optica spectrum disorders and multiple sclerosis. Methods: Fractional anisotropy, mean, axial, and radial diffusivity and T1/T2-weighted ratio maps were obtained from patients with seropositive neuromyelitis optica spectrum disorders, multiple sclerosis, and healthy controls ( n = 20 each group). White matter damage was assessed as function of ventricular distance within progressive concentric bands. Results: Compared to healthy controls, neuromyelitis optica spectrum disorders patients had similar fractional anisotropy, radial and axial diffusivity, increased mean diffusivity ( p = 0.009–0.013) and reduced T1/T2-weighted ratio ( p = 0.024–0.037) in all bands. In multiple sclerosis, gradient of percentage lesion volume and intra-lesional mean and axial diffusivity were higher in periventricular bands. Compared to healthy controls, multiple sclerosis patients had reduced fractional anisotropy ( p = 0.001–0.043) in periventricular bands, increased mean ( p < 0.001), radial ( p < 0.001–0.004), and axial diffusivity ( p = 0.002–0.008) and preserved T1/T2-weighted ratio in all bands. Conclusion: White matter damage is higher at periventricular level in multiple sclerosis and diffuse in neuromyelitis optica spectrum disorders. Fractional anisotropy preservation, associated with increased mean diffusivity and reduced T1/T2-weighted ratio may reflect astrocyte damage.